FROM ASENG TO OSING “HISTORİCAL REVIEW OF THE EXISTENCE AND DYNAMICS OF CHINESE ETHNIC IDENTITY IN BANYUWANGI” - Mahfud; Dian Arief Pradana; Herdiana Dyah Susanti (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
The existence of Chinese ethnicity in Banyuwangi is estimated since the 17th century, the existence of Chinese in Blambangan has certainly experienced an interesting dynamic process to be revealed, especially how the history of the existence and change of ethnic Chinese identity itself, from Aseng who incidentally is a foreigner to Osing who is a native of Banyuwangi . A certain society always presents stereotyped views. Likewise with Chinese identity in Banyuwangi. Referring to the view of cultural studies, identity is entirely a socio-cultural construction. No identity can emerge outside of cultural representation or acculturation. The dynamics of social change in the cultural dimension refers to cultural changes in society such as contact with other cultures which causes cultural diffusion and borrowing. This identity change phenomenon can be seen in the Chinese ethnic identity in Banyuwangi Regency. The history of the Chinese ethnic in Banyuwangi as a whole has experienced ups and downs caused by the conditions of Indonesian domestic and foreign socio-political culture, placing the Chinese ethnic in an uncertain position, and tending to become victims of Indonesia's social and political situation which is always turbulent. This then causes the ethnic Chinese to always be faced with difficult conditions that affect their existence as an ethnic group. As Chinese people in Banyuwangi, they generally admit to being confused about choosing whether to retain their distinctive Chinese (hereditary) characteristics, or have to completely abandon everything they received from their ancestors and completely merge into the majority society. This paper aims to discuss how the emergence of the history of ethnic Chinese in Banyuwangi Regency, formerly known as Blambangan, and how the dynamics of the development of social change for ethnic Chinese in Banyuwangi.